FRI0116 Habitual Physical Activity in People with Rheumatoid Arthritis within The First Five Years of Diagnosis. (15th July 2016) - Elramli, A.S.; Paul, L.; Gill, J.M.; Gray, C.M.; Porter, D.; McFadyen, A.K.
Abstract : Background: Physical activity (PA) plays an important role in the management of RA in improving function, reducing risk of CVD and promoting a sense of well-being. Objectives: To identify habitual PA profiles, including time spent sedentary, and self-efficacy to perform exercise. To investigate the association between PA and demographic variables, functional status, quality of life and self-efficacy. Methods: Data were obtained from 76 people within the first five years of RA diagnosis and who were attending Rheumatology clinics in Glasgow, UK. Demographic data (age, sex, level of education, and employment) were recorded. Anthropometric data (Waist to hip ratio (WHR) and body mass index (BMI)) were assessed. PA profiles; the number of steps per day (step count) and time spent sedentary (sitting or lying down) were recorded for seven days using an ActivPAL activity monitor. Quality of life was measured with the Rheumatoid Arthritis Quality of Life questionnaire (RAQoL); functional status was assessed with a six minute walk test (6MWT), Health Assessment Questionnaire (HAQ) and hand grip strength (using a dynamometer). Self-efficacy was evaluated using the Self-efficacy to Regulate Exercise Scale. The data were analysed using Pearson's correlations, t test and ANOVA as appropriate. A multiple linear regression model was developed to investigate the baseline variables that contributed significantly to PA. Statistical significance was accepted at p<0.05. Results: Of the 76 participants, 63 were women, mean age was 56 (± 15) years, 42.1% were in employment, WHR was 0.84 (± 0.09) and BMI was 27.4 (± 5.6) kg/m 2 . The mean 6MWT was 351 (±122.7) m and hand grip strength was 21.6 (±11.3) kg, the RAQoL score was 11.7 (±8.7) and HAQ score was 1.1 (±0.84). Self-efficacy was 40.3% (± 25%). Step count was 7236 (± 2142) steps/day, and time spent sedentary was 18 (± 1.7) hrs. There were weak but statistically significant relationships between step count and: sedentary time (r =-0.238, P=0.039), HAQ (r =-0.318, P=0.005), 6MWT (r=0.265, P=0.021) and self-efficacy, (r=0.284, P=0.013). A multiple linear regression model showed significant association between step count and sedentary time (P=0.033), HAQ (P=0.002) and WHR (P=0.045). There was a significant weak association between sedentary time and self-efficacy (r=-0.262, P=0.022). No other variables showed significant correlations with step count or sedentary time. Conclusions: PA, as determined by steps count is about 30% lower than 10.000 steps/day recommended for health benefits. A higher step count was associated with reduced sedentary time, lower physical disability and WHR. Other variables not included in this analysis, such as pain, and fatigue may also be associated. Participants were within the first five years of being diagnosed with RA however, it is important to maintain/improve levels of PA as the disease progresses to improve the cardiovascular health and functioning of the individual. References: Plasqui. The role of physical activity in rheumatoid arthritis. Physiol Behav 2008;94:270 Tudor-Locke, et al.How many steps/day are enough? For adults.Int JBehav Nutr Phys, 2011;8:79 Disclosure of Interest: None declared